Low‐Temperature High‐Rate Capabilities of Lithium Batteries via Polarization‐Assisted Ion Pathways. (7th March 2018) - Teranishi, Takashi; Katsuji, Naoto; Chajima, Keisuke; Yasuhara, Sou; Inohara, Masahiro; Yoshikawa, Yumi; Yasui, Shintaro; Hayashi, Hidetaka; Kishimoto, Akira; Itoh, Mitsuru
Abstract: On‐board vehicle applications dictate the need for improved low‐temperature power densities of rechargeable batteries. Integration of high‐permittivity artificial dielectric solid electrolyte interfaces (SEIs) into the lithium ion battery architecture is a promising path to satisfy this need. The relationship between the permittivity of various artificial dielectric SEIs and the resulting high‐rate capability at low temperatures is investigated. Room‐temperature studies reveal a weak relationship between these variables. However, at low temperatures, the correlation between the larger permittivity of the dielectric SEIs and the greater high‐rate capabilities of the cells is striking. The high‐rate capabilities for pulsed laser deposition‐synthesized cathode thin films with various BaTiO3 (BTO) SEIs covering configurations are evaluated. A remarkable improvement in the high‐rate capability is observed for LiCoO2 (LCO) modified with dot BTOs, while the rate capability for planar BTO (fully covered LCO) is weakened significantly. A series of experimental results prove that a large polarization, P, in the dielectric SEIs intensified with permittivity accelerates interfacial charge transfer near the dielectrics–LCO–electrolyte triple junction. Abstract : Correlation between the polarizabilities of dielectric solid electrolyte interfaces and improved high‐rate capabilities of lithium ion batteries is demonstrated. A series of experimental results indicate that the negative charges at the intensified electric dipole moment near the dielectrics–active materials–electrolyte triple junction attract the positively charged Li +, allowing the formation of fast ion pathways at low temperatures.